2009
DOI: 10.1038/pcan.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

First-year costs of treating prostate cancer: estimates from SEER-Medicare data

Abstract: Pharmacologic therapies are currently being evaluated for the prevention of prostate cancer (PCa). As additional clinical data become available regarding their benefits and risks, an examination of their economic impact will also be important. The purpose of this study was to estimate mean per patient PCa-related costs during the first year following diagnosis and to examine the extent to which initial therapies are used, by initial cancer stage. Our data show that health-care costs were significant and varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
2
24
0
5
Order By: Relevance
“…Other studies also examined initial treatment costs only. 21,22 Zeliadt et al 9 used SEER-Medicare, but their study was more focused on how prostate-specific antigen testing affected initial treatment costs. By using a different database, Krupski et al examined costs of care specifically related to androgen deprivation therapy.…”
Section: Original Article 5396mentioning
confidence: 99%
“…Other studies also examined initial treatment costs only. 21,22 Zeliadt et al 9 used SEER-Medicare, but their study was more focused on how prostate-specific antigen testing affected initial treatment costs. By using a different database, Krupski et al examined costs of care specifically related to androgen deprivation therapy.…”
Section: Original Article 5396mentioning
confidence: 99%
“…Details related to the sample selection procedures for the PCa and non-cancer cohorts have been described in a prior study examining first-year PCa costs. 4 …”
Section: Data Source and Patient Populationmentioning
confidence: 99%
“…Although recent studies have examined PCa-related costs from a Medicare perspective using either the Surveillance, Epidemiology, and End Results (SEER)-Medicare data, [4][5][6] the Medicare 5% public use files, 7 or the CaPSURE database, 8 there are few recent studies examining costs in phases of care beyond initial treatment and stratified by cancer stage. Furthermore, many of the studies identified only examine costs for patients diagnosed with early stage PCa.…”
Section: Introductionmentioning
confidence: 99%
“…A beválogatási és kizárási kritériumok alkalmazását köve-tően összesen 15 közlemény (4 európai és 11 észak-amerikai) került kiválasztásra, amelyek jellemzőit és eredményeit az 1. táblázatban mutatjuk be [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Külön elemezzük az európai és az Egyesült Államokból, illetve Kanadából származó kutatásokat, aminek okai az adatbázisok betegszámainak jelentős eltérései, a módszertani különbségek, továbbá az eltérő szakmai protokollok és egészségügyi költségek.…”
Section: Eredményekunclassified
“…Az első 3 terápiás év összes költsége 113 158 SEK, amelyhez hozzáadódnak még a gyógyszerköltségek (7600 SEK/ év), továbbá a szövődményes incontinentia miatti költsé-gek (20 000 SEK/év) [14]. [16,17,18,19,20,21,22,23]. A SEER-adatbázis előnye, hogy egy-egy kutatásba nagyszámú beteg (minden bemutatott európai kutatásnál nagyobb) bevonását teszi lehetővé, illetve több mint 30 évre visszamenőleg tartalmazza a betegek adatait.…”
Section: Terápiás Fázisok áTlagköltségeiunclassified